The Chronicler's code the rise and fall of Juda's army in the book of Chronicles - Klein, Neriah (2017)
This article focuses on the numbers given in the book of Chronicles for the armies of the Judean kings, with an emphasis on the sequence of the first four kings of Judah. It argues that these numbers were inserted by the Chronicler according to a clear and systematic pattern. Specifically, they are used as a literary device to express a pattern of changes in royal power, in which power increased from the time of Rehoboam's reign until Jehoshaphat, before gradually decreasing until the reign of Ahaz.